Resection of primary leiomyosarcoma of the inferior vena cava (IVC) with reconstruction: A case series and review of the literature. Issue 3 (8th October 2014) - Wachtel, Heather; Jackson, Benjamin M.; Bartlett, Edmund K.; Karakousis, Giorgos C.; Roses, Robert E.; Bavaria, Joseph E.; Fraker, Douglas L.
Abstract Background Leiomyosarcoma of the inferior vena cava (IVC) is a rare tumor which presents a unique surgical challenge. We present a series of six cases of leiomyosarcoma resection performed with IVC reconstruction. Methods Retrospective chart review was performed for patients undergoing initial operative resection of primary leiomyosarcoma with IVC reconstruction, at a tertiary care center. Results Between 2005–2013, six patients underwent resection with reconstruction. Half were female, and the mean age at presentation was 57 ± 15.4 years. Three patients required en bloc resection with adjacent organs. Three patients were resected on venovenous bypass, and one on cardiopulmonary bypass. Three underwent IVC patch repair (bovine pericardium, n = 2; saphenous vein, n = 1), and three had IVC reconstruction with graft (Dacron, n = 1; PTFE, n = 1; aortic homograft, n = 1). All achieved grossly negative margins. Median disease‐free survival was 34 months (IQR 7–52 months), and median disease‐specific survival was 51 months (IQR 20–108). Five year disease‐free and disease‐specific survival rates were 30% and 66.7%, respectively. Conclusions Leiomyosarcomas of the IVC present a technical challenge to the surgeon. Careful preoperative workup and a collaborative team consisting of experienced cardiac and vascular surgeons and surgical oncologists can allow for a safe and successful operation despite extensive tumor involvement. J. Surg. Oncol. 2015 111:328–333. © 2014 Wiley Periodicals, Inc.